Leading the way : women in power - Howell, Janet; Howell, Theresa (Candlewick Press, 2019)
Contains fifty illustrated brief biographies of female leaders in government and politics, such as Ida B. Wells, Betty Ford, and Kamala Harris. Illustrated icons representing virtuous qualities such as empathy, diligence, and courage, are highlighted on each profile relaying the individual's strengths. Includes a guide for young women to get involved in government and politics.